PENGARUH KUALITAS PELAYANAN DAN BRAND IMAGE TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN PADA PT. MITRA PINASTHIKA MUSTIKA (Studi Kasus Pelanggan Ahass MPM Motor Bojonegoro) - Alfian, Frismandana; Jojok Dwiridho, Tjahjono (Jurnal Bisnis Indonesia, 2021)
This study aims to determine whether Service Quality and Brand Image affect Customer Loyaltythrough Customer Satisfaction. This research is motivated by the emergence of many motorcyclerepair shops which create a competition to attract and retain customers. The quality of serviceprovided and a good corporate image is judged to increase each customer's satisfaction and isexpected to be able to deduce loyalty in using the company's services.In this study the respondents used are regular customers, what is meant by regular customersare users of workshop services who have used service services more than twice at AHHAS MPMMotor Bojonegoro. The number of samples is determined by the calculation of Slovin formula andobtained as many as 110 respondents. The analytical method used in this study is path analysis,which has previously been tested for validity, reliability, and classic assumptions.The results of this study indicate that service quality has a direct effect on customer loyaltyand indirect effect on customer loyalty through customer satisfaction. While brand image has nodirect effect on customer loyalty, but brand image has an indirect effect on customer loyalty throughcustomer satisfaction Keywords: Service Quality, Brand Image, Customer Loyalty, Customer Satisfaction  DOI : https://doi.org/10.33005/jbi.v12i1.2605